The use of clinoptilolite as a catalyst in the gasoline engines - (:unkn) unknown (SILA SCIENCE, 2012)
Practical aplication of lean burn gasoline engines on cars has been increasing in recent years. The lean burn gasoline engine is operated under high air/fuel ratio to improve fuel economy. However reduction of emissions from the exhaust under oxygen rich condition is very difficult to achieve. For this purpose, the studies on zeolite catalysts are increasing. In this study, natural zeolite of clinoptilolite type was prepared for use as a catalyst in gasoline engines. 9245 ppm (about 0.93%) copper were deposited on zeolite by various chemical treatments. Ion-exchanged zeolite catalyst was tested at an SI engine. Maximum carbonmonoxide conversion efficiency achieved was 39.5% at 2300 rpm. Maximum hydrocarbon conversion efficiency achieved was 31.5% at 1500 rpm.
Keywords: Natural zeolite; Clinoptilolite; Gasoline engine; Catalyst; Exhaust emissions; ZEOLITE CATALYSTS; NOX REDUCTION; EXHAUST; HYDROCARBONS; EMISSION; NO(X); C3H6; FUEL